A prática educativa do agente de combate às endemias no cotidiano da vigilância em saúde da Ilha de Parintins no Amazonas: desafios e possibilidades da educação popular em saúde - Campos, Raimundo Sidnei dos Santos (2019)
The research is about educational practices performed by Endemic Diseases Combat Agents (Agentes de Combate às Endemias - ACEs) in the daily activities of Health Surveillance in Parintins’ Island, Amazonas. As a goal comprehend of the meanings in the educational practices of ACE in the control activities and endemic prevention, Through the challenges and possibilities of popular education actions in health surveillance, Identifying the agents' positions in the light of the knowledge, service practices, ministerial guidelines and working protocols from initiatives presented in Amazon context. The research, of a qualitative nature, is based on the theory and practice of Popular Education. The technique of data collection was based on observations and interviews. For a better understanding of the meanings attributed to educational practices, It was resorted from the Indiciary Paradigm method, by Carlo Gunzburg (1989). Therefore, the analysis favored empirical and documentary evidence, captured by the particularities and relations with the investigated problem. The field research was carried out in the conty of Parintins in the State of Amazonas. The subjects of the research are ACEs, labours belonging to the staff of the Health Surveillance Coordination of the Municipal Health Department. The educational practices of the agents were analyzed based on evidence indicating the agent's experiences and knowledge and the light of guidelines and working protocols established for health control, prevention and surveillance. We affirm that: approaching the understanding of the subjects of the popular educational practice creates opportunities for dialogue and exchange of experiences, bringing out more clearly the contribution thoughts and actions of ACEs as subjects of knowledge and convictions in the relations of individuals, groups and community, contributing to the construction and strengthening of practices that may enable the experience of popular surveillance in the Amazonian context. The results pointed out that the popular educational practice happens with more force and concreteness in the home visits that integrate the work routines of the agents in the community. Practices play an important role in all actions of health surveillance, especially for the possibility of arousing dialogic relations and exchange of experiences between the agents of the health system and the users of the services. The results also indicated that the educational practice of ACEs can be a mediator of knowledge that emerge in the local context, which suggests, in the field of control of endemics and health surveillance, important elements to think about the reorientation of work routines in domiciliary spaces in order to understand the local knowledge, the sociocultural identity of the individuals to whom the actions are directed, and the complexity of the demands and particularities of the Amazonian context. The thesis aims to offer contributions to think about and problematize the educational practice of the ACE, through the challenges of the attributions of its field of action and the possibilities of doing this in the perspective of popular education in health.